Cadmium(II) Removal from Aqueous Solution Using Microporous Eggshell: Kinetic and Equilibrium Studies - Behzad Shamsi Zadeh; Hossein Esmaeili; Rauf Foroutan (Indonesian Journal of Chemistry, 2018)
Heavy metals are soluble in the environment and can be dangerous for many species. So, removal of heavy metals from the water and wastewater is an important process. In this study, an adsorbent made of eggshell powder was employed to remove cadmium ions from aqueous solution. A number of parameters were studied including pH of the aqueous solution, adsorbent dosage, contact time, the initial concentration of cadmium ion and mixing rate. The best efficiency for the removal of Cd(II) was obtained 96% using this adsorbent. The optimal parameters were ambient temperature of 30 °C, mixing rate of 200 rpm, pH of 9, an adsorbent dosage of 5 g/L and initial concentration of cadmium was 200 ppm. In order to study the kinetics of adsorbent, the pseudo-first-order and pseudo-second-order kinetic models and intra-particle diffusion model were applied. According to the pre-determined correlation coefficients (R2), the pseudo-second-order kinetic model showed a better correlation between the kinetic behaviors of the adsorbent. Furthermore, to study the equilibrium behavior of adsorbent, Langmuir and Freundlich models used and both models showed high efficiency in isotherm behavior of the adsorbent. So, this adsorbent can be used as a natural and cheap adsorbent.